Evaluation of Special Programme - in Selected Districts of M.P. and Orissa - Planning Commission (Planning Commission)
The study was confined to two districts of Orissa, viz. Phulbani and Sambalpur and two districts of Madhya Pradesh viz. Jabalpur and Sidhi. Special programmes are in operation/ in all these districts. DPAP, ITDA and IRD are in progress in Phulbani; SFDA and IRD in Sambalpur; SFDA and IRD in Jabalpur and DPAP and IRD in Sidhi. Two blocks of each of these two districts were selected for in-depth assessment of these programmes. The blocks so chosen were Khajuripada and Harbhanga in Phulbani; Jharsuguda and Kirmira in Sambalpur; Shahpura and Panagarh in Jabalpur and Deosar and Waidhan in Sidhi.
National Committee on Backward Areas, Planning Commission, Government of India